Inovasi Desain Kemasan Untuk Meningkatkan Penjualan Produk Umkm Healthy Tasty Food Surabaya - Bimo Sandya Prima Sakti (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Packaging design innovation is a crucial strategy in boosting product sales. Innovation is the practical development and improvement of an initial discovery into a technique that can be used. This research aims to enhance the sales of banana chips produced by the Small and Medium Enterprises (UMKM) Healthy Tasty Food Surabaya through packaging design innovation implemented by interns from WMK.The research methods encompassed interviews, observations, brainstorming, active participation, and documentation. The results indicate that the implemented packaging design innovation successfully increased the sales of Healthy Tasty Food Surabaya's banana chips, as evidenced by a surge in orders and sales.The packaging design innovation involved alterations in shape, color, and packaging material. The new packaging was designed to be more appealing and informative, incorporating bright colors and attractive graphics. Additionally, the new packaging was equipped with comprehensive product information, including nutritional content and expiration date.The positive impact of this packaging design innovation is evident in the increased number of orders and sales for the UMKM, as well as improved customer satisfaction and product image. This research provides a significant contribution to similar UMKMs by uncovering the potential for sales enhancement through the improvement of their product packaging design quality.